(untitled) (Oxford,Boston, 2000)
"...an interesting and varied collection of current ideas, stressing the importance of prevention of occupational injury and disease while at the same time highlighting the lack of national and international recognition of the problem. [...] ...its multidisciplinary approach to prevention and management of industrial injury would be of similar use to any physiotherpists working in the field of occupational health."Physiotherapy, January 2001
Keywords: Industrial hygiene,Industrial accidents,Accidents, Occupational,Vệ sinh công nghiệp,Tai nạn công nghiệp,Tai nạn, nghề nghiệp; prevention & control,Kiểm soát và ngăn ngừa